Persistent or new symptoms 1 year after a single high dose of vitamin D3 in patients with moderate to severe COVID-19 - Fernandes, Alan L.; Sales, Lucas P.; Santos, Mayara D.; Caparbo, Valeria F.; Murai, Igor H.; Pereira, Rosa M. R. (Frontiers in Nutrition, 2022)
Purpose. To investigate the reported persistent or new symptoms one-year after a single dose of 200,000IU of vitamin D3 and hospitalization in patients with moderate to severe COVID-19. Methods. This is a post-hoc, exploratory analysis from a multicenter, double-blind, placebo-controlled, randomized clinical trial from two hospitals in Sao Paulo, Brazil. Discharged patients were followed for up to one-year and evaluated by telephone interview at six and 12 months. The primary and secondary outcomes were previously published. This post-hoc exploratory secondary outcomes are the persistent or new symptoms and quality-of-life (QoL) at post-viral stage of COVID-19. Generalized estimating equations (GEE) for repeated measures with Bonferroni’s adjustment were used for testing outcomes. Results. We randomized 240 patients of which 144 were included in this study (the vitamin D3 [n=71] or placebo [n=73] group). The mean (SD) age was 54.3(13.1) years, and BMI was 32.4(6.5) kg/m2. Fever demonstrated a significant main effect of time (P < 0.001) with reduction from baseline to six (52 to 0) and 12 months (52 to 0). No significant differences between-groups were observed for fever, cough, fatigue, fever, myalgia, joint pain, runny nose, nasal congestion, sore throat, hypertension, diabetes, cardiovascular disease, rheumatic disease, asthma, chronic obstructive pulmonary, chronic kidney disease, QoL, new or persistent symptoms up to one-year of follow-up. Conclusion. The findings do not support the use of 200,000IU of vitamin D3 compared to placebo for the management of persistence or new symptoms, and QoL reported by moderate to severe patients after hospitalization for COVID-19.